Physically Transient Gelatin-Based Memristors of Buildable Logic Gates - Lu Wang; Yuting Wang; Wenhao Li; Zhiqiang Gao; Yutong Han; Dianzhong Wen (Gels, 2025)
Moore’s Law is being challenged, as the use of transistors has limitations in terms of physical materials, energy consumption, performance, and economics. To continue Moore’s Law, people have put forward many ideas, one of which is to find smaller devices to replace CMOS transistors. Memristor-based digital logic circuits open new avenues for exploring advanced computing architectures. In this paper, a biomemristor with the structure of Al/gelatin:Au NPs/Al/gelatin was fabricated using gelatin as the substrate and the host material of the dielectric layer. The device has a large switching current ratio, good stability, and physical transient characteristics. The device can be dissolved by soaking in deionized water for 5 min. In addition, the device successfully realizes the functions of NAND and NOR logic gates. It provides an effective method for research on green electronic devices with logic functions.